2019
DOI: 10.1007/s11218-019-09496-4
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and social anxiety experiences in university learning situations

Abstract: This study examines how individuals' engagement in bullying at school and at university relates to the anxiety they feel in general and in various learning situations in which students interact during their higher education. It was predicted that, of the individuals who have experiences of bullying (in the role of bully, victim, or in a dual role as bully-victim), those who have been subjected to bullying experience more anxiety than do those who have no experience with bullying. A nationally representative sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 50 publications
1
19
0
7
Order By: Relevance
“…In their literature review, Pörhölä et al (2019) demonstrate the existence of studies to show that being bullied by peers is associated with academic problems and deficiencies in academic achievements in childhood and adolescence, however, they also argue this association may fall away as students grow up. Holt et al (2014), for example, found that past bullying experiences were not associated with academic performance in college.…”
Section: Contributions To Construct Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…In their literature review, Pörhölä et al (2019) demonstrate the existence of studies to show that being bullied by peers is associated with academic problems and deficiencies in academic achievements in childhood and adolescence, however, they also argue this association may fall away as students grow up. Holt et al (2014), for example, found that past bullying experiences were not associated with academic performance in college.…”
Section: Contributions To Construct Validitymentioning
confidence: 99%
“…Although bullying has been widely recognized as a serious issue in elementary and secondary school (e.g., Craig et al 2009;Currie et al 2012;Nansel et al 2001) and in the workplace (e.g., Keashly and Harvey 2005), and its long-term consequences on the psychosocial functioning, academic motivation and study ability of individuals have been found to reach from school year experiences even to higher education (e.g., Espelage et al 2016;Holt et al 2014;Pörhölä et al 2019;Young-Jones et al 2015), relatively little research has examined the prevalence and forms of bullying victimization and perpetration at the university level (Lund and Ross 2016). However, existing studies clearly indicate that bullying does occur among higher education students, and occurrence rates vary substantially between individual studies (Cowie et al 2013;Lund and Ross 2016;Marraccini et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, bullying does not only occur in primary school (Aulia, 2016). The academia also experiences bullying in the university or higher education (Pörhölä et al, 2019). In this context of "academic bullying", the experience does not exclusively happen between students, but also perpetration by the university personnel toward the students…”
Section: Academic Bullyingmentioning
confidence: 99%
“…Sayangnya, perundungan tidak hanya terjadi di sekolah dasar dan menengah (Aulia, 2016). Insan akademis juga mengalami perundungan di jenjang pendidikan tinggi (Pörhölä et al, 2019). Dalam konteks "perundungan akademik", hal tersebut tidak hanya terjadi antar mahasiswa, namun juga dilakukan (Pörhölä et al, 2020), and bullying among the faculty personnel themselves (Meriläinen et al, 2019).…”
Section: Perundungan Akademikunclassified
“…Related to students' academic engagement, there exists a broadening discussion and also concerns about students' well-being both in basic and in higher education [30] that is constructed between students and the various learning contexts and interactions in them [31]. Several studies have identified factors that are related to students' decreased well-being both in basic and in higher education contexts, for example, learning difficulties, study-related burnout [32,33], experiences of bullying [34][35][36] and loneliness in peer relations [37,38]. These concerns encourage to think actively about the factors contributing to students' well-being and especially the structures and pedagogical practices in educational institutions.…”
Section: Current Pedagogical Challenges In Basic and Higher Educationmentioning
confidence: 99%